Building From the Ground Up: The Key to Health and Well-Being in Schools (LEARNing Landscapes, 2017)
In this interview, Sharon Klein, the Head of School at St. George’s School of Montreal, discusses how health and well-being are integrated in the curriculum and school life. Since its beginning in 1930, St. George’s has operated on six founding principles, the first of which is “health comes first.” Ms. Klein describes how this principle is being applied—yoga, mindfulness, exercise literacy—and further describes how they have developed the Core 5 Program, based on current research, to meet the needs of today’s students. She concludes by sharing her vision of health and well-being in the future.
Keywords: health; well-being; yoga; mindfuless; exercise literacy; core 5